Vietnam : Science, Technology, and Innovation Report 2020 - World Bank (World Bank, Washington, DC, 2021)
The science, technology, and innovation (STI) report provide analytical support for Vietnam’s upcoming ten-year STI strategy 2021-2030 and the socio-economic development strategy (SEDS) 2021-2030. The STI report has been prepared in response to a request from the Ministry of Science and Technology (MOST). The new STI strategy is expected to contribute to a strengthened national innovation system (NIS) that will promote a more innovation-driven enterprise sector, and in turn lead to sustained high-growth in Vietnam. As the Coronavirus disease 2019 (COVID-19) triggered economic shock continues to spread globally and its impact deepens in Vietnam, the importance of innovation and technology adoption for business resilience as well as for productive growth has been amplified. This report will highlight specific changes in policies and present institutional options to strengthen technology adoption and innovation in enterprises to inform the new STI strategy 2021-2030 and the SEDS 2021-2030 in section one. Towards this end, section two presents the conceptual framework for the study. A brief overview of the current STI policy institutional framework is presented in section three. Section four reviews the state of Vietnam’s developing NIS and identifies the recurring gaps that hinder Vietnamese enterprises from adopting and applying technology. The coherence and quality of STI policies - the last pillar of the NIS - is examined in section five. Section six reviews the implication of the emerging domestic and global shifts and how they inform the new STI strategy. Section seven provides a roadmap of priority reform actions that are needed to reset the new STI strategy towards business innovation and technology adoption.